Melatonin modulates the fetal cardiovascular defense response to acute hypoxia - Thakor, Avnesh S (J Pineal Res, 2015)
Experimental studies in animal models supporting protective effects on the fetus of melatonin in adverse pregnancy have prompted clinical trials in human pregnancy complicated by fetal growth restriction. However, the effects of melatonin on the fetal defense to acute hypoxia, such as that which may occur during labor, remain unknown. This translational study tested the hypothesis, in vivo, that melatonin modulates the fetal cardiometabolic defense responses to acute hypoxia in chronically instrumented late gestation fetal sheep via alterations in fetal nitric oxide (NO) bioavailability. Under anesthesia, 6 fetal sheep at 0.85 gestation were instrumented with vascular catheters and a Transonic flow probe around a femoral artery. Five days later, fetuses were exposed to acute hypoxia with or without melatonin treatment. Fetal blood was taken to determine blood gas and metabolic status and plasma catecholamine concentrations. Hypoxia during melatonin treatment was repeated during in vivo NO blockade with the NO clamp. This technique permits blockade of de novo synthesis of NO while compensating for the tonic production of the gas, thereby maintaining basal cardiovascular function. Melatonin suppressed the redistribution of blood flow away from peripheral circulations and the glycemic and plasma catecholamine responses to acute hypoxia. These are important components of the fetal brain sparing response to acute hypoxia. The effects of melatonin involved NO-dependent mechanisms as the responses were reverted by fetal treatment with the NO clamp. Melatonin modulates the in vivo fetal cardiometabolic responses to acute hypoxia by increasing NO bioavailability.